BAHAN MANIPULATIF UNTUK MENGENALKAN MATEMATIKA KEPADA SISWA SEKOLAH DASAR - Aprilia Kurniawati & Budiyono (LIMIT - Pendidikan Matematika, 2011)
Mathematic at elementary school is a basic learning as the important fundament for the following level of learning. One of the Competency Standards of primary school graduates in mathematics is understanding the concept of frac-tions, ratio in problem solving, as well as its use in daily life practices. Mathe-matics as the study of abstract objects is of course very difficult to be understood by elementary school students who have not been able to think of formal, because its orientation is still associated with concrete objects. For that to her simplified difficult concepts, presenting material that is relatively abstract becomes more real, more concretely explain the concepts necessary to use manipulative materials to convey would be better understood by students. Manipulative materials are materials that can be manipulated by hand, which is held, turned, moved, arranged or laid out, rotated, cut into pieces. With manipulative materials are students expected to be more active and became interested in mathematics to be taught the teachers. Manipulative materials are used to explain certain properties associated with the operation of arithmetic and geometry properties, and considering the the facts. Key word: manipulative materials, Mathematic, student of elementary school